Independently getting off the floor: a feasibility study of teaching people with stroke to get up after a fall. (22nd March 2019) - Dean, Sarah G; Poltawski, Leon; Warmoth, Krystal; Goodwin, Victoria A; Stiles, Victoria H; Taylor, Rod S
No abstract available